Financial Distress and Financial Performance on Stock Return with Firm Size as Moderating Variable - Sebastianus Laurens; Susi Dwi Mulyani (University of Merdeka Malang, 2022)
This study analyses the factors that impact the stock return, whether financial distress, earnings (per share), and price to book value affect the stock return. The sample data used are secondary data with a sample using 28 listed manufacturing companies with a decade of 2012-2021 with a total sample of 209, with 71 data being excluded because they do not fit the criteria-the data processed with moderated regression analysis using statistic software. The statistic test showed earnings (per share), financial distress and price to book value have no impact on stock returns. This research also uses the firm size as moderating variable and the Investment Opportunity Set as the control variable. Firm size has no role in moderating the independent variables on stock returns. Investment Opportunity Set (IOS) affects stock returns.